Partial Connections - Strathern, Marilyn (Oxford Altamira, 2004)
Available with a new Preface, Marilyn Strathern's seminal book challenges the routine ways in which anthropologists have thought about the complexity and quantity of their materials, focusing on a problem normally thought of as commonplace; that of scale and proportion. Revealing unexpected replications in modes of thought and in the presentation of ambiguous images, Strathern has fashioned a unique contribution to the anthropological corpus.
Keywords: Philosophy